Systemic risk and the macroeconomy: An empirical evaluation - Giglio, Stefano; Kelly, Bryan; Pruitt, Seth (Journal of Financial Economics, 2016)
This article studies how systemic risk and financial market distress affect the distribution of shocks to real economic activity. We analyze how changes in 19 different measures of systemic risk skew the distribution of subsequent shocks to industrial production and other macroeconomic variables in the US and Europe over several decades. We also propose dimension reduction estimators for constructing systemic risk indexes from the cross section of measures and demonstrate their success in predicting future macroeconomic shocks out of sample.